Radiation cooling porous ceramic material and preparation method thereof
Through the nitriding combustion synthesis method of Si3N4-BN porous ceramic materials, the problems of high temperature, high cost and poor stability of existing ceramic materials are solved, and efficient radiation cooling effect is achieved, which is suitable for building cooling.
Patent Information
- Application Number
- CN202411788799.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
AI Technical Summary
The existing radiation-cooled ceramic materials are prepared in high temperature environments, which are costly and have poor chemical and mechanical stability, making it difficult to cope with extreme environments.
Si3N4-BN radiation-cooled porous ceramic material is used, and through nitriding combustion synthesis, Si powder, B2O3 powder and α-Si3N4 are used as raw materials, and the vibration absorption of BN B-N bond and Si3N4 in the atmospheric window band is improved to improve the optical performance of the material.
High solar reflectivity and high infrared emissivity are achieved. The material's solar reflectivity in the 0.3-2.5μm band is greater than 0.8, and the infrared emissivity in the 8-13μm atmospheric window band is greater than 0.9, which is suitable for building cooling.
Smart Images

Figure CN119613126A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of radiation cooling materials, and in particular to a radiation cooling porous ceramic material and a preparation method thereof. Background Art
[0002] Energy crisis and climate change are two major challenges facing mankind in the 21st century. At present, electricity consumption for refrigeration accounts for about 10% of the world's total electricity consumption, and it is expected that by 2050, the demand for electricity for refrigeration will triple. Traditional refrigeration technology consumes electricity and increases greenhouse gas emissions. In the past 30 years, carbon dioxide emissions from space refrigeration have more than doubled to nearly 1 billion tons, which will further aggravate global warming. In view of this, finding and developing new refrigeration technologies is of great significance for saving energy and promoting the process of carbon neutrality.
[0003] Radiative cooling technology is a new type of refrigeration technology that is energy-free and environmentally friendly. It achieves a cooling effect below ambient temperature by reflecting solar radiation heat and radiating its own heat to outer space with a temperature of about 3K in the atmospheric window band (8-13μm). The research on radiative cooling materials was initially mainly based on nanophotonic structures of multilayer inorganic films. However, the production technology of this structure is complex and costly, and its application is limited, especially in the field of construction. Therefore, in recent years, researchers have explored the use of alternative materials such as organic polymers, such as polymer-metal composite films, porous polymer coatings and foams, and polymer-ceramic particle coatings. However, organic polymers increase their solar absorption under complex environmental conditions (such as ultraviolet rays, heat, water, and environmental chemicals), thereby reducing their cooling efficiency and may even cause the material to be heated. In addition, metals (such as silver and aluminum) used in polymer or inorganic radiative cooling structures may be oxidized or sulfided by chemicals in the air, thereby reducing their solar reflectivity. Ceramic materials have shown unique potential in the field of radiative cooling due to their many performance advantages such as stability and durability, and are expected to become important refrigeration materials in construction and other application fields.
[0004] At present, the research and development of radiation cooling ceramic materials has been gradually carried out, and the material systems involved are mostly oxide porous ceramic materials. For example, inspired by the scale structure of white beetles in nature, Cao Zhiyin's team at the City University of Hong Kong has developed an Al2O3 ceramic material with a micro-nano hierarchical pore structure. The material exhibits excellent sunlight reflection performance (close to 99.6%) and efficient mid-infrared emission capability (about 96.5%). However, the preparation process of this radiation cooling porous ceramic material mostly requires a long-term high temperature environment, and the sintering raw materials are mostly nano oxides, which are expensive and not easily available; in addition, the chemical stability, high temperature stability and mechanical stability of this oxide ceramic are poor, and it is difficult to cope with more harsh extreme environments. Nitride ceramic materials, especially silicon nitride ceramics, have higher stability than oxide ceramics and are a very promising radiation cooling ceramic material. For example, Li Jiangtao and others used an efficient and low-energy combustion synthesis process to prepare a β-silicon nitride radiation cooling ceramic powder with a reflectivity (R Solar )≥0.80, and the emissivity (ε) in the atmospheric window band (8-13μm) ≥0.85 (patent document number CN118108191A). However, this ceramic powder needs to be compounded with a polymer to be prepared into a coating or film for thermal management, and the optical properties of the material also need to be improved. Therefore, it is necessary to develop a silicon nitride-based radiation cooling porous ceramic material with both high solar reflectivity and infrared emissivity. The present invention comes from this. Summary of the invention
[0005] In order to solve at least one of the above-mentioned technical problems, the purpose of the present invention is to provide a Si3N4-BN radiation cooling porous ceramic material and a preparation method thereof, which utilizes the multiple scattering of sunlight by Si3N4, BN and porous ceramic pores, and the vibration absorption of the BN bond of BN and the Si-N bond of Si3N4 in the "atmospheric window" (8-13μm) band to improve the optical properties of the porous ceramic material. The ceramic material has a sunlight reflectivity greater than 0.8 in the 0.3-2.5μm band and an infrared emissivity greater than 0.9 in the 8-13μm atmospheric window band, which can meet the practical application of building cooling.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0007] One of the purposes of the present invention is to provide a radiation cooling porous ceramic material, wherein the ceramic material comprises, by mass percentage, 0-30wt% of boron nitride nanosheets, 65-100wt% of silicon nitride and 0-5wt% of residual silicon.
[0008] Furthermore, the porosity of the ceramic material is 30-70%, and the average pore size is 0-2 μm.
[0009] Furthermore, the solar reflectivity of the ceramic material in the 0.3-2.5 μm band is greater than 0.8, and the infrared emissivity in the 8-13 μm atmospheric window band is greater than 0.9.
[0010] Furthermore, the solar reflectivity of the ceramic material in the 0.3-2.5 μm band is greater than 0.9, and the infrared emissivity in the 8-13 μm atmospheric window band is greater than 0.95.
[0011] Another object of the present invention is to provide a method for preparing a radiation cooling porous ceramic material, wherein the ceramic material is any one of the ceramic materials described above, and the preparation method comprises:
[0012] Weigh raw material powders consisting of Si, B2O3, α-Si3N4 and rare earth oxide according to mass percentage, and mix the raw material powders by ball milling to obtain slurry;
[0013] The uniformly mixed slurry is placed in an oven for drying and sieving to obtain green powder, and the sifted green powder is subjected to uniaxial cold pressing to obtain a ceramic green body;
[0014] Placing the ceramic green body in a graphite mold filled with chemical furnace powder, and placing the graphite mold in a combustion synthesis reactor, filling the combustion synthesis reactor with nitrogen at a certain pressure, and inducing a combustion synthesis reaction through an external heat source to obtain the radiation cooling porous ceramic material;
[0015] Wherein, the chemical furnace powder is a mixed powder of Si and β-Si3N4.
[0016] The present invention adopts the nitridation combustion synthesis method, uses silicon powder (Si) and boron oxide (B2O3) as reaction raw materials, and α-silicon nitride (α-Si3N4) as diluent. Based on the chemical reaction equation (1), the Si3N4-BN porous ceramic material with high solar reflectivity and high infrared emissivity is synthesized for the first time.
[0017] Reaction formula (1) Si+B2O3+N2+α-Si3N4→Si3N4+BN
[0018] After further study, it was found that the reaction path can be seen in chemical reaction equations (2) and (3) and Figure 1 :
[0019] First, according to reaction (2), Si reacts with N2 to form silicon nitride (β-Si3N4), which is the key to the entire combustion synthesis process. Under high temperature conditions, B2O3 melts and distributes on the surface of the newly generated β-Si3N4 particles to form an amorphous layer.
[0020] Then, BN is generated based on the chemical reaction between B2O3 and Si3N4 (i.e., reaction (3)), and the generated BN is distributed around β-Si3N4, and finally a Si3N4-BN radiation cooling porous ceramic material is obtained.
[0021] 3Si(s)+2N2(g)=Si3N4(s) Reaction formula (2)
[0022] Si3N4(s)+2B2O3(l)=4BN(s)+3SiO2(s) Reaction formula (3)
[0023] Furthermore, in the raw material powder, Si powder accounts for 10-60wt%, B2O3 powder accounts for 0-67wt%, α-Si3N4 powder accounts for 14-70wt%, and the mass ratio of Si / α-Si3N4 in the raw material powder is 3 / 7-3 / 2.
[0024] Furthermore, the mass ratio of Si and β-Si3N4 in the chemical furnace powder is m(Si) / m(β-Si3N4)=3 / 7~3 / 2.
[0025] Furthermore, the particle size of Si powder in the raw material powder is 1.5-5 μm.
[0026] Furthermore, the content of rare earth oxide in the raw material powder is ≤5wt%; and / or
[0027] The rare earth oxides in the raw material powder include Y2O3 and CeO2.
[0028] Furthermore, the mass ratio of grinding balls to raw material powder during ball milling is 1:1 to 4:1, and the ball milling time is 1 to 4 hours; and / or
[0029] The pressure during uniaxial cold pressing is 10-30Mpa; and / or
[0030] The drying conditions are drying at 60-110°C for 12-24 hours.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The Si3N4-BN radiation cooling porous ceramic material of the present invention utilizes the multiple scattering of sunlight by Si3N4, BN and porous ceramic pores, and the vibration absorption of the BN bond of BN and the Si-N bond of Si3N4 in the "atmospheric window" (8-13μm) band to improve the optical properties of the porous ceramic material. The material has a sunlight reflectivity greater than 0.8 in the 0.3-2.5μm band and an infrared emissivity greater than 0.9 in the 8-13μm atmospheric window band, which can meet the practical application of building cooling and has broad application prospects. The Si3N4-BN radiation cooling porous ceramic material is synthesized in situ in a nitrogen atmosphere by a combustion synthesis method with simple process, high efficiency, low cost and near zero energy consumption, using low-cost Si powder and B2O3 powder as raw materials, α-Si3N4 as a diluent, rare earth oxide as a sintering aid, and chemical furnace powder (mixed powder of Si and β-Si3N4). The preparation method is low-cost, short-cycle and near zero energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 is the XRD pattern of the Si3N4-BN radiation cooling porous ceramic material in Example 2 of the present invention;
[0035] Figure 2 is the solar reflectivity of the Si3N4-BN radiation cooling porous ceramic material in Example 2 of the present invention in the 0.3-2.5 μm band;
[0036] Figure 3 It is the infrared emissivity of the Si3N4-BN radiation cooling porous ceramic material in Example 2 of the present invention in the 2.5-25μm band. DETAILED DESCRIPTION
[0037] In view of the deficiencies in the prior art, the inventors of this case, after long-term research and extensive practical discoveries, proposed a radiation-cooled porous ceramic material based on air combustion synthesis and a preparation method thereof.
[0038] The following is a further explanation of the technical solution, its implementation process and principle, etc. in conjunction with the preferred embodiments and the accompanying drawings. It should be noted that the following embodiments are only auxiliary explanations of the present invention and should not be used to limit the protection scope of the present invention.
[0039] Example 1
[0040] 17.0 g of Si powder with a particle size of 1.5 μm, 11.4 g of α-Si3N4 powder with a particle size of 1 μm, 66.6 g of B2O3 powder with a particle size of 75 μm are used as raw materials, and 5 g of Y2O3 powder with a particle size of 50 nm is used as a sintering aid, wherein m(Si) / m(α-Si3N4) is about 3 / 2, and the raw material powder is 100 g; ethanol is used as a grinding medium to ball mill the powder mixture for 2 hours; after mixing evenly, the mixture slurry is dried for 24 hours, and the powder mixture is sieved through a 100-mesh sieve; a hydraulic press is used to sieve the powder mixture Uniaxial cold pressing with a pressure of 10MPa to obtain a ceramic green body; the ceramic green body is placed in a graphite mold filled with chemical furnace powder, the chemical furnace powder is composed of Si and β-Si3N4, m(Si) / m(β-Si3N4)=3 / 2; the graphite mold filled with chemical furnace powder and ceramic green body is placed in a 20L combustion synthesis reactor, and the reactor is passed through a nitrogen pressure of 5MPa; the powder mixture is ignited by a tungsten coil buried in the titanium powder on the top of the mold, and the ignition current is 10A; after the reaction is completed, the porous ceramic block is taken out and its surface is ground and polished. The phase composition of the porous ceramic sample is β-Si3N4, α-Si3N4, BN and residual Si, of which the BN content is about 30wt%; the porosity is about 65%, and the pore size is 1μm; the solar reflectivity in the 0.3-2.5μm band is about 0.85, and the infrared emissivity in the 8-13μm band of the atmospheric window is 0.95.
[0041] Example 2
[0042] 11g Si powder with a particle size of 5μm, 25g α-Si3N4 powder with a particle size of 1μm, 59g B2O3 powder with a particle size of 75μm are used as raw materials, and 5g CeO2 powder with a particle size of 50nm is used as a sintering aid, wherein m(Si) / m(α-Si3N4) is about 3 / 7, and the raw material powder is 100g; ethanol is used as a grinding medium to ball mill the powder mixture for 2 hours; after mixing evenly, the mixture slurry is dried for 24 hours, and the powder mixture is sieved through a 100-mesh sieve; a hydraulic press is used to perform uniaxial cold pressing on the powder mixture , the pressure is 30MPa, and a ceramic green body is obtained; the ceramic green body is placed in a graphite mold filled with chemical furnace powder, the composition of the chemical furnace powder is Si and β-Si3N4, m(Si) / m(β-Si3N4)=3 / 2; the graphite mold filled with chemical furnace powder and ceramic green body is placed in a 20L combustion synthesis reactor, and the reactor is passed through a nitrogen pressure of 4MPa; the powder mixture is ignited by a tungsten coil buried in the titanium powder on the top of the mold, and the ignition current is 10A; after the reaction is completed, the porous ceramic block is taken out and its surface is ground and polished. The phase composition of the porous ceramic sample is β-Si3N4, BN and a very small amount of residual Si, of which the BN content is about 20wt%; the porosity is about 56%, and the pore size is 0.8μm; the solar reflectivity in the 0.3-2.5μm band is about 0.83, and the infrared emissivity in the 8-13μm band of the atmospheric window is 0.94.
[0043] Example 3
[0044] 25.3 g of Si powder with a particle size of 1.5 μm, 16.8 g of α-Si3N4 powder with a particle size of 1 μm, 52.9 g of B2O3 powder with a particle size of 75 μm are used as raw materials, and 5 g of Y2O3 powder with a particle size of 50 nm is used as a sintering aid, wherein m(Si) / m(α-Si3N4) is 3 / 2, and the raw material powder is 100 g; ethanol is used as a grinding medium to ball mill the powder mixture for 2 hours; after mixing evenly, the mixture slurry is dried for 24 hours, and the powder mixture is sieved through a 100-mesh sieve; a hydraulic press is used to single-crystal the powder mixture. Axial cold pressing with a pressure of 20MPa to obtain a ceramic green body; the ceramic green body is placed in a graphite mold filled with chemical furnace powder, the chemical furnace powder is composed of Si and β-Si3N4, m(Si) / m(β-Si3N4)=3 / 7; the graphite mold filled with chemical furnace powder and ceramic green body is placed in a 20L combustion synthesis reactor, and the reactor is passed through a nitrogen pressure of 4MPa; the powder mixture is ignited by a tungsten coil buried in the titanium powder on the top of the mold, and the ignition current is 10A; after the reaction is completed, the porous ceramic block is taken out and its surface is ground and polished. The phase composition of the porous ceramic sample is β-Si3N4, α-Si3N4, BN and residual Si, of which the BN content is about 20wt%; the porosity is about 57%, and the pore size is 0.78μm; the solar reflectivity in the 0.3-2.5μm band is about 0.83, and the infrared emissivity in the 8-13μm band of the atmospheric window is 0.93.
[0045] Example 4
[0046] 25.8 g of Si powder with a particle size of 1.5 μm, 17.2 g of α-Si3N4 powder with a particle size of 1 μm, 54.0 g of B2O3 powder with a particle size of 75 μm are used as raw materials, and 3 g of Y2O3 powder with a particle size of 50 nm is used as a sintering aid, wherein m(Si) / m(α-Si3N4) is 3 / 2, and the raw material powder is 100 g; ethanol is used as a grinding medium to ball mill the powder mixture for 2 hours; after mixing evenly, the mixture slurry is dried for 24 hours, and the powder mixture is sieved through a 100-mesh sieve; a hydraulic press is used to single-crystal the powder mixture. Axial cold pressing with a pressure of 20MPa to obtain a ceramic green body; the ceramic green body is placed in a graphite mold filled with chemical furnace powder, the chemical furnace powder is composed of Si and β-Si3N4, m(Si) / m(β-Si3N4)=3 / 7; the graphite mold filled with chemical furnace powder and ceramic green body is placed in a 20L combustion synthesis reactor, and the reactor is passed through a nitrogen pressure of 3MPa; the powder mixture is ignited by a tungsten coil buried in the titanium powder on the top of the mold, and the ignition current is 10A; after the reaction is completed, the porous ceramic block is taken out and its surface is ground and polished. The phase composition of the porous ceramic sample is β-Si3N4, α-Si3N4, BN and residual Si, of which the BN content is about 20wt%; the porosity is about 55%, and the pore size is 0.76μm; the solar reflectivity in the 0.3-2.5μm band is about 0.82, and the infrared emissivity in the 8-13μm band of the atmospheric window is 0.91.
[0047] Example 5
[0048] 25.3 g of Si powder with a particle size of 1.5 μm, 16.8 g of α-Si3N4 powder with a particle size of 1 μm, 52.9 g of B2O3 powder with a particle size of 75 μm are used as raw materials, and 5 g of CeO2 powder with a particle size of 50 nm is used as a sintering aid, wherein m(Si) / m(α-Si3N4) is 3 / 2, and the raw material powder is 100 g; ethanol is used as a grinding medium to ball mill the powder mixture for 2 hours; after mixing evenly, the mixture slurry is dried for 24 hours, and the powder mixture is sieved through a 100-mesh sieve; a hydraulic press is used to single-crystal the powder mixture. Axial cold pressing with a pressure of 20MPa to obtain a ceramic green body; the ceramic green body is placed in a graphite mold filled with chemical furnace powder, the chemical furnace powder is composed of Si and β-Si3N4, m(Si) / m(β-Si3N4)=3 / 7; the graphite mold filled with chemical furnace powder and ceramic green body is placed in a 20L combustion synthesis reactor, and the reactor is passed through a nitrogen pressure of 4MPa; the powder mixture is ignited by a tungsten coil buried in the titanium powder on the top of the mold, and the ignition current is 10A; after the reaction is completed, the porous ceramic block is taken out and its surface is ground and polished. The phase composition of the porous ceramic sample is β-Si3N4, α-Si3N4, BN and residual Si, of which the BN content is about 20wt%; the porosity is about 57%, and the pore size is 0.78μm; the solar reflectivity in the 0.3-2.5μm band is about 0.83, and the infrared emissivity in the 8-13μm band of the atmospheric window is 0.93.
[0049] Comparative Example 1
[0050] 25.3g Si powder with a particle size of 1.5μm and 16.8g α-Si3N4 powder with a particle size of 1μm are used as raw materials, 5g Y2O3 powder with a particle size of 50nm is used as a sintering aid, wherein m(Si) / m(α-Si3N4) is 3 / 2, and the raw material powder is 100g; use ethanol as a grinding medium to ball-mill the powder mixture for 2 hours; after mixing evenly, the mixture slurry is dried for 24 hours, and the powder mixture is sieved through a 100-mesh sieve; use a hydraulic press to perform uniaxial cold pressing on the powder mixture at a pressure of 20MPa to obtain a ceramic green body; place the ceramic green body in a graphite mold and then in a 20L combustion synthesis reactor with a nitrogen pressure of 4MPa; the powder mixture is ignited by a tungsten coil buried in the titanium powder on the top of the mold, and the ignition current is 10A; after the reaction is completed, the porous ceramic block is taken out and its surface is polished. The phase composition of the porous ceramic sample is β-Si3N4; the porosity is about 51%, the pore size is 0.70μm; the solar reflectivity in the 0.3-2.5μm band is about 0.78, and the infrared emissivity in the 8-13μm band of the atmospheric window is 0.92. It can be seen that after eliminating the chemical furnace powder, the infrared emissivity of the porous ceramic filler obtained in the 8-13μm band of the atmospheric window still reaches more than 0.9, which is not significantly lower than other embodiments, but the solar reflectivity in the 0.3-2.5μm band has decreased, lower than 0.8, which is more obvious than other embodiments.
[0051] It should be noted that the test methods involved in the above embodiments can all refer to the existing national standards, industry standards or enterprise standards, and will not be described in detail.
[0052] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0053] The use of headings and sections in this disclosure is not meant to limit the disclosure; each section may apply to any aspect, embodiment, or feature of the disclosure.
[0054] Throughout this disclosure, where a composition is described as having, containing, or comprising particular components, or where a process is described as having, containing, or comprising particular process steps, it is contemplated that the compositions taught by the present invention also consist essentially of or consist of the recited components, and that the processes taught by the present invention also consist essentially of or consist of the recited process steps.
[0055] Unless specifically stated otherwise, use of the terms "include," "includes," "including," "have," "has," or "having" should generally be construed as open ended and non-limiting.
[0056] It should be understood that the order of the various steps or the order in which a particular action is performed is not very important, as long as the teachings of the present invention remain operable. In addition, two or more steps or actions may be performed simultaneously.
[0057] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. A radiation cooling porous ceramic material, characterized in that: The ceramic material comprises, by mass percentage, 0-30wt% of boron nitride nanosheets, 65-100wt% of silicon nitride and 0-5wt% of residual silicon.
2. The radiation cooling porous ceramic material according to claim 1, characterized in that: The porosity of the ceramic material is 30-70%, and the average pore size is 0-2 μm.
3. The radiation cooling porous ceramic material according to claim 1, characterized in that: The solar reflectivity of the ceramic material in the 0.3-2.5 μm band is greater than 0.8, and the infrared emissivity in the 8-13 μm atmospheric window band is greater than 0.
9.
4. The radiation cooling porous ceramic material according to claim 1 or 3, characterized in that: The solar reflectivity of the ceramic material in the 0.3-2.5 μm band is greater than 0.9, and the infrared emissivity in the 8-13 μm atmospheric window band is greater than 0.
95.
5. A method for preparing a radiation cooling porous ceramic material, characterized in that: The ceramic material is the ceramic material according to any one of claims 1 to 4, and the preparation method comprises: Weigh raw material powders consisting of Si, B2O3, α-Si3N4 and rare earth oxide according to mass percentage, and mix the raw material powders by ball milling to obtain slurry; The uniformly mixed slurry is placed in an oven for drying and sieving to obtain green powder, and the sifted green powder is subjected to uniaxial cold pressing to obtain a ceramic green body; Placing the ceramic green body in a graphite mold filled with chemical furnace powder, and placing the graphite mold in a combustion synthesis reactor, filling the combustion synthesis reactor with nitrogen at a certain pressure, and inducing a combustion synthesis reaction through an external heat source to obtain the radiation cooling porous ceramic material; Wherein, the chemical furnace powder is a mixed powder of Si and β-Si3N4.
6. The preparation method according to claim 5, characterized in that: In the raw material powder, Si powder accounts for 10-60wt%, B2O3 powder accounts for 0-67wt%, α-Si3N4 powder accounts for 14-70wt%, and the mass ratio of Si / α-Si3N4 in the raw material powder is 3 / 7-3 / 2.
7. The preparation method according to claim 5, characterized in that: The mass ratio of Si to β-Si3N4 in the chemical furnace powder is m(Si) / m(β-Si3N4)=3 / 7-3 / 2.
8. The preparation method according to claim 5, characterized in that: The particle size of Si powder in the raw material powder is 1.5-5 μm.
9. The preparation method according to claim 5, characterized in that: The content of rare earth oxide in the raw material powder is ≤5wt%; and / or The rare earth oxides in the raw material powder include Y2O3 and CeO2.
10. The preparation method according to claim 5, characterized in that: During the ball milling process, the mass ratio of grinding balls to raw material powder is 1:1 to 4:1, and the ball milling time is 1 to 4 hours; and / or The pressure during uniaxial cold pressing is 10-30Mpa; and / or The drying conditions are drying at 60-110°C for 12-24 hours.
Citation Information
Patent Citations
Powder with spectral selectivity as well as preparation method and application thereof
CN118108191A